Advances in Native Chemical Ligation–Desulfurization: A Powerful Strategy for Peptide and Protein Synthesis. Issue 66 (8th October 2018) - Jin, Kang; Li, Xuechen
Abstract: Cysteine‐based native chemical ligation (NCL) has been a very powerful approach for convergent synthesis of peptides and proteins. However, owing to the low abundance of cysteine (Cys) in proteins, applications of NCL in protein chemical synthesis are limited. To expand the peptide ligation toolbox, NCL followed by desulfurization has been developed to enable peptide ligation at Xaa‐Ala conjunctions, that is, formal "alanine ligation". In this regard, effective peptide desulfurization methods are critical. This Concept article summarizes the development of different desulfurization strategies for peptide and protein chemical synthesis. Abstract : The development of different desulfurization methods is summarized in this Concept article, including metal‐based desulfurization, metal‐free radical‐based desulfurization, photochemical desulfurization and phosphine‐boron (P‐B) desulfurization. Some of these methods have been effectively used in protein/peptide chemical synthesis and modification.